Identification of emotional expressiveness in facial photographs over 36 h of extended vigilance in healthy young men—a preliminary study. Issue 2 (17th February 2017) - Ginani, Giuliano Emerenciano; Pradella-Hallinan, Marcia; Pompéia, Sabine
ABSTRACT: Changes in sleep patterns negatively influence some emotional responses, but their effects on facial expressiveness identification are unclear. To investigate these effects, 21 young, healthy, male volunteers of intermediate chronotype evaluated emotional expressiveness of faces depicting 6 basic emotions in 5 emotional gradients every 4 h over 36 h of continuous wakefulness. To measure attention and mood we used the Psychomotor Vigilance test and the Positive and Negative Affect Schedule Expanded, respectively. We found effects of emotional gradient for all types of emotions (100% > 80% > 60% > 40% > 20%) during all tested periods, with no indications of circadian effects. The only emotional rating to be affected was disgust, which was progressively blunted throughout the experiment. This effect did not parallel homeostatic and circadian changes in mood, alertness or attention. We conclude that identifying disgust on facial photographs is particularly sensitive to lack of sleep irrespective of sleep-induced changes in mood and attention in males.